2016
DOI: 10.1016/j.bbrc.2015.11.084
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with liposome-coupled glypican-3-derived epitope peptide stimulates cytotoxic T lymphocytes and inhibits GPC3-expressing tumor growth in mice

Abstract: Because therapeutic manipulation of immunity can induce tumor regression, anti-cancer immunotherapy is considered a promising treatment modality. We previously reported that glypican-3 (GPC3), an oncofetal antigen overexpressed in hepatocellular carcinoma (HCC), is a useful target for cytotoxic T lymphocyte (CTL)-mediated cancer immunotherapy, and we have performed clinical trials using the GPC3-derived peptide vaccine. Although vaccine-induced GPC3-peptide-specific CTLs were often tumor reactive in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In 2012, Xu and co‐workers developed a similar liposomal system embedded with MHC II complexes to display antigenic OVA, which resulted in CD4 + T cell activation and anti‐OVA antibody production . Later, Nakatsura and co‐workers used liposomes displaying glypican‐3 (GPC3) antigens with CpG ODN adjuvants to induce GPC3‐specific CTLs and inhibit GPC3‐expressing hepatocellular carcinoma . The following year, Wyatt and co‐workers employed liposomes with envelope glycoproteins conjugated to their surfaces to activate B cells against HIV‐1 …”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…In 2012, Xu and co‐workers developed a similar liposomal system embedded with MHC II complexes to display antigenic OVA, which resulted in CD4 + T cell activation and anti‐OVA antibody production . Later, Nakatsura and co‐workers used liposomes displaying glypican‐3 (GPC3) antigens with CpG ODN adjuvants to induce GPC3‐specific CTLs and inhibit GPC3‐expressing hepatocellular carcinoma . The following year, Wyatt and co‐workers employed liposomes with envelope glycoproteins conjugated to their surfaces to activate B cells against HIV‐1 …”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…Nakatsura and co-workers conducted a study to effectively enhance the antitumor reactivity of GPC3-derived epitope peptides in vivo, and reported that liposome-coupled GPC3 peptides induced peptide-specific CTLs at a lower dose than did a conventional vaccine emulsified in incomplete Freund's adjuvant. 146 Additionally, programmed death-1/programmed death ligand-1 blockade has been reported to augment the antitumor effects of the GPC3-derived peptide vaccine by increasing the immune response of vaccine-induced CTLs. 147 Through this work, Nakatsura and co-workers have provided a foundation for the clinical development of combination therapy involving the use of GPC3 peptide vaccines with other medications.…”
Section: Gpc3-derived Peptide/dna Vaccinesmentioning
confidence: 99%
“…However, molecular therapy remains a challenge mainly due to lack of specific targets. Use of the GPC-3 antigen as a target for HCC has been investigated with siRNA (47), vaccines (48,49), T lymphocytes (50)(51)(52), and anti-GPC-3 antibodies in vitro and in vivo (53,54). Some advances on the use of GPC-3 as the novel target for HCC therapy have been made (55).…”
Section: Gpc-3 As a Novel Target For Hcc Therapymentioning
confidence: 99%